2022
DOI: 10.3390/nu14224788
|View full text |Cite
|
Sign up to set email alerts
|

Food Composition Data and Tools Online and Their Use in Research and Policy: EuroFIR AISBL Contribution in 2022

Abstract: Food, nutrition, and health are linked, and detailed knowledge of nutrient compositions and bioactive characteristics is needed to understand these relationships. Additionally, increasingly these data are required by database systems and applications. This communication aims to describe the contribution to databases and nutrition fields as well as the activities of EuroFIR AISBL; this member-based, non-profit association was founded to ensure sustained advocacy for food information in Europe and facilitate imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…All this chemical diversity that remains invisible in common epidemiology may have an important effect on our health ( 42 ). Numerous initiatives are trying to compile this information from validated peer-review sources, such as Phenol-Explorer ( 43 ), but the current lack of harmonization introduces important challenges ( 44 ).…”
Section: The Problems Of Current Fcdbsmentioning
confidence: 99%
“…All this chemical diversity that remains invisible in common epidemiology may have an important effect on our health ( 42 ). Numerous initiatives are trying to compile this information from validated peer-review sources, such as Phenol-Explorer ( 43 ), but the current lack of harmonization introduces important challenges ( 44 ).…”
Section: The Problems Of Current Fcdbsmentioning
confidence: 99%
“…Over the last decade, there has been an increase in the number of studies and research on the connection between these different sectors. Specialized food databases can provide information and data for the creation of sustainable nutritional models to reduce the now growing number of chronic diseases [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data should comply with FAIR principles (findability, accessibility, interoperability, and reusability). With new emerging technologies, infrastructures are emerging that can make this process adequate [ 11 , 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global harmonization in methodology is certainly needed among regional databases to allow data interchange. One important initiative in Europe was the formation of the EuroFIR Association Internationale Sans But Lucratif (AISBL, meaning an international non-profit association), which had a mission to “promote harmonization and exploitation of high-quality food composition data and foster cooperation and participation in development with national compiler organizations” [ 15 ]. Formed in 2009, EuroFIR AISBL advocates for improved data quality, storage, and accessibility for food information in Europe and the rest of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Formed in 2009, EuroFIR AISBL advocates for improved data quality, storage, and accessibility for food information in Europe and the rest of the world. A prior bibliometric analysis showed that over 100 papers published since 2005 mentioned EuroFIR, and they were mainly published in journals dealing with Agricultural and Biological Sciences, Nursing, Medicine, and Chemistry [ 15 ].…”
Section: Introductionmentioning
confidence: 99%